Effects of dengue virus type-2 serotype (DENV-2) on the expression profile of matrix metalloproteinases in THP-1, monocyte cells and their roles in endothelial dysfunctions: protective effect of atorvastatin - Niranjan, Rituraj; Vidhyapriya, Pitchavel; Murugasamy, Vyshali; Muthukumaravel, Subramanian; Kumar, Ashwani (Frontiers in Cellular and Infection Microbiology, 2025)
Dengue viral fever is one of the most important arboviral infections, particularly in tropical and subtropical regions. In a dengue infection, monocyte-mediated matrix metalloproteases are speculated to be implicated in tissue damage and vascular leakage. However, the exact mechanisms are largely unknown. In the present study, we investigated the expression profiles of MMPs in primary monocytes and in THP-1 cells infected with all dengue virus serotypes. The mechanism of MMP-mediated anti-viral effect of atorvastatin was also investigated in detail on dengue virus-induced expression profiles of mRNA and VEGF. We found elevated mRNA expressions profiles of MMP-2, MMP-9, and MMP-14 in DENV-infected THP-1 cells compared to the uninfected control group. Interestingly, these upregulated expressions of MMPs were reversed by atorvastatin. Similar patterns of mRNA expressions were also observed of MMPs and VEGF members in NS1-injected mice. Atorvastatin downregulated the MMP and VEGF expressions in this NS1-injected mouse model. Next, to prove the role of immune cells in causing endothelial dysfunctions, secretome obtained from dengue virus-induced monocytes was exposed to endothelial cells. Interestingly, this secretome has an elevated expression of pro-apoptotic and angiogenic markers like caspases, angiopoietins, VEGF, and their receptor genes in endothelial (HUVEC) cells. These changes were reversed by atorvastatin in a dose-dependent manner. Furthermore, the mechanistic role of MMP-9 in causing apoptosis and angiogenesis in endothelial cells was established. Thus, we suggested that DENV-2 might cause monocyte-mediated angiogenesis and apoptosis, making endothelial dysfunctions which may resemble the mechanism of pathogenesis of dengue shock syndrome (DHF/DSS). Additionally, our finding shows that atorvastatin has MMPs’ inhibitory potential against dengue, which may be adopted in clinical trials against severe dengue viral disease. The current findings are interesting; however, further studies may be needed to adopt the current findings in the future.